Genomic Differences in Thyroid Cancers From Primary Sites Versus Distant Metastases in Individual Patients: A Clinical Perspective and Preliminary Report - Lin, Yen‐Bo; Hu, Hsiang‐Wei; Chung, An‐Ko; Lu, Jin‐Ying; Wu, Wan‐Chen; Chiu, I‐Hsuan; Chu, I; Lin, Chia‐Chi; Lee, Jih‐Hsiang; Nien, Feng‐Jung; Chen, Kuen‐Yuan; Wu, Ming‐Hsun; et al. (Head & neck, 2025)
ABSTRACT Background Distant metastasis is a leading cause of thyroid cancer (TC)‐related deaths. Genetic profiling is typically limited to one sample per patient due to cost and sampling‐risk concerns. Differences between samples from thyroid and distant metastasis within individual patients are unclear. Methods Patients with TC and distant metastasis were recruited for genetic analysis. Results Using a TC‐specific NGS panel, 66 specimens from 29 patients were analyzed, identifying 16 mutations and 4 fusions, including two novel fusions (FGFR2–SHTN1 and RFTN1–BRAF). Genetic alterations differed between primary and metastatic sites in nine patients (31%), predominantly in additional oncogenic alterations (89%). More genetic alterations were found at the primary site in three patients and metastatic sites in four. Distinct mutations were found in two patients. A longer time interval between specimen acquisitions was significantly associated with genetic discrepancies (p = 0.032). Conclusion Patterns of genetic discrepancies between primary and metastatic TC vary, offering valuable insights for clinical practice.